Characteristic patterns of white matter tract injury in sport-related concussion: An image based meta-analysis - Sarah C. Hellewell; Vy P.B. Nguyen; Ruchira N. Jayasena; Thomas Welton; Stuart M. Grieve (NeuroImage: Clinical, 2020)
Sports-related concussion (SRC) is sustained by millions of people per year, yet the spatiotemporal patterns of white matter (WM) injury remain poorly understood. Several SRC studies have implemented the standardised approach Tract-Based Spatial Statistics (TBSS). The aim of this image-based meta-analysis was to identify consensus patterns of SRC-related WM injury across TBSS studies. We included studies comparing the diffusion MRI measurement fractional anisotropy (FA) in SRC or subconcussive injury vs. controls using TBSS, as FA is the most frequently examined diffusion tensor imaging metric. Authors of eligible studies were contacted to request unthresholded statistical map outputs from TBSS, and image-based meta-analyses were performed using Seed-Based d-Mapping. Eight studies contributed to our meta-analyses, comprising 174 SRC or subconcussive injury participants and 160 controls. Our primary meta-analysis (n = 8), encompassing subjects with acute SRC (n = 2), chronic SRC (n = 4) and subconcussive injuries (n = 2) revealed dominant bilateral increased FA in the superior longitudinal fasciculus (SLF) and internal capsule. Subconcussive injury was associated with small clusters of increased and decreased FA in the arcuate fasciculus compared to control. In acute SRC, we found diffuse foci of raised FA at WM/grey matter border-zone associated with the bilateral SLF and right inferior fronto-occipital fasciculus. In contrast, chronic SRC had a pattern of deep WM alteration, asymmetrically located in the right optic radiations and arcuate fasciculus. Our findings represent the most powerful analysis of TBSS data in SRC, supporting the use of this approach to analyse diffusion data. TBSS is sensitive to WM abnormalities resulting from SRC or subconcussive injury over a range of temporal and clinical scenarios. Our data show spatially concordant patterns of WM injury unique to subconcussive, acute and chronic phases, highlighting the future utility of diffusion MRI for concussion diagnosis.